The influence factors of e-logistics towards customer satisfaction in China - Lisha, Guo (2019)
Since from last decade, the e-logistic industry of China facing different issues due to high volume worldwide. To address these issues, this study is quantity and use regression to test the hypotheses.11 introduced a framework to mitigate various issues of e-logistic in China. Therefore, the prime objective of the current study is to examine factors influencing e-logistics in China. To achieve this objective, the current study examines the effect of distribution rate (DR), transit time ( TT ), E-payment ( EP ), E-traceability ( ET), Information and Communication Technology ( ICT ) on E-logistics Customer Satisfaction ( ELCS ). This study, each items will be tested by survey. Moreover, there are 501 useful responds from e-logistics customers who live in Shaanxi province. Five hypotheses were formulated. Generally, the results were found to support the hypotheses. DR, TT, EP, ET, ICT have positive relationship with ELCS. Additionally, ICT was seen to partially mediate between EPET and ELCS. The findings of this study imply that the managers of e-logistics performance in China need to pay more attention on DR, TT, EP, ET and ICT, as they can be used to improve e-logistics activities. Especially, ICT, which is a key influence factor and can partially mediate between EPIET and ELCS, this could attract more investment and improved.